Short-Term Storage of Six Penicillins and Cephalothin in Microdilution Trays for Antimicrobial Susceptibility Tests - Barry, A. L. (1976)
To perform microdilution antimicrobial susceptibility tests efficiently, broth dilutions of the antimicrobial drugs should be prepared in large batches and stored frozen until needed. Studies were carried out to document the stability of ampicillin, benzylpenicillin, carbenicillin, methicillin, oxacillin, nafcillin, and cephalothin in microdilution trays during storage at −20 and −60 C. No significant deterioration was noted after 21 days of storage, as detected by bioassay and by replicate minimal inhibitory concentration determinations with control organisms. No significant differences were noted moreover between trays stored for three weeks at −20 C and those stored at −60 C. The microdilution technique was found to be a highly reproducible method for quantitative determination of antimicrobial susceptibility.